2022
DOI: 10.22141/pjs.12.1.2022.323
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle dysfunction, sarcopenia and sarcopenic obesity in patients with chronic obstructive pulmonary disease

Abstract: Background. Chronic obstructive pulmonary disease (COPD) is often associated with musculoskeletal dysfunction, including skeletal muscle dysfunction, sarcopenia, osteoporosis, and obesity. The purpose was to assess skeletal muscle status and determine the prevalence of sarcopenia and sarcopenic obesity in patients with COPD. Materials and methods. 66 patients with COPD and 35 healthy subjects had been examined. Sarcopenia was established using EWGSOP2 criteria, and sarcopenic obesity was defined in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
1
0
2
Order By: Relevance
“…Другой цитокин, интерлейкин-15 (ИЛ-15), также экспрессируется в скелетных мышцах и вносит свой вклад в метаболизм липидов, обеспечивая взаимодей ствие между мышечной и жировой тканью. Показано, что уровень интерлейкина-8 (ИЛ-8), который участвует в процессах ангиогенеза, возрастает при увеличении физической активности [4,[16][17][18].…”
Section: Fig 1 the Interplay Between Bone Muscle And Adipose Tissueunclassified
See 1 more Smart Citation
“…Другой цитокин, интерлейкин-15 (ИЛ-15), также экспрессируется в скелетных мышцах и вносит свой вклад в метаболизм липидов, обеспечивая взаимодей ствие между мышечной и жировой тканью. Показано, что уровень интерлейкина-8 (ИЛ-8), который участвует в процессах ангиогенеза, возрастает при увеличении физической активности [4,[16][17][18].…”
Section: Fig 1 the Interplay Between Bone Muscle And Adipose Tissueunclassified
“…Такой эффект не только обеспечивает положительные метаболические воздействия, но и увеличивает длину теломер. В связи с этим некоторые исследователи рассматривают иризин как «миокин молодости и жизни» [17,20].…”
Section: Fig 1 the Interplay Between Bone Muscle And Adipose Tissueunclassified
“…Similar alterations in gut microbiota have also been observed in adults with asthma. Fedosenko et al (2014), Masik et al (2019), Zolnikova et al (2020), andOzimek et al (2022), have observed changes in gut microbiota in adult patients with bronchial asthma, including an increase in the proportion of Proteobacteria and a…”
mentioning
confidence: 99%